Chronic Inflammatory Demyelinating Polyradiculoneuropathy - Shije, Jeffrey; Brannagan, Thomas H., III (Seminars in Neurology, 2019)
Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is a relatively common autoimmune disorder affecting the peripheral nerves and nerve roots, often causing progressive or recurrent weakness with diminished reflexes. Electrodiagnostic (EDx) studies, cerebral spinal fluid (CSF) analysis, and nerve biopsy may help provide supportive evidence for the diagnosis. Most cases have a favorable response to one of the three first-line treatments: corticosteroids, IV immunoglobulin (IVIG) and plasmapheresis. Responses to these treatments may vary among individual patients. There is evidence that a small percentage of CIDP patients with IgG class 4 (IgG4) autoantibodies to paranodal proteins have characteristic clinical features and poorer response to IVIG. Chemotherapy and other immunomodulatory agents, as well as hematopoietic stem cell transplantation, may be considered in refractory cases. The degree of disability varies, and most patients require ongoing treatment to maintain stable disease, although long-term remission or cure may be achieved in some patients.
Keywords: chronic inflammatory demyelinating polyradiculoneuropathy; CIDP; inflammatory neuropathy